Tutela coletiva e julgamento repetitivo: suas interações e reconstruções no enfrentamento da litigiosidade - Pinto, Lucas José Bezerra (2024)
Since the massification and homogenization of social and legal relations in contemporaneity, which, in their procedural projection, triggered the "explosion of litigation" and the "crisis of the justice system" currently experienced in the jurisdictional field, civil procedure has undergone movements of reflection and reconstruction in recent decades. In Brazilian law, these adaptations and refinements were structurally consolidated in the procedural microsystems of class actions and of judgment of repetitive cases. Although they share a similar background, as well as technical and operational confluences, they did not receive from the 2015 Civil Procedure Code a normatization that established a clear dialogue between their institutes, semiconcealing the virtual relations existing between the models. Following this problem, this work explores these potential interactions in and beyond the process. For this, it follows not the most common path - which, paradoxically, begins with the post-established procedural allegories (duality of collective interests and repetitive issues) - but returns to the starting point of the problem: the phenomenology that encompasses and underpins them (litigation, litigiousness, and litigiosity). In this sense, before considering the repercussions and procedural formations suitable for a better jurisdictional response to the problems related to massification, the collective and repetitive phenomenon that surrounds them is investigated, reconstructing the current and potential intra-procedural relations from the valuation of their contours, trajectories, and inherent limitations. Based on the hypothesis that the insufficiencies of the microsystem of judgment of repetitive cases can be mitigated by a co-participation of collective guardianship in addressing massified litigiousness, especially from the perspective of the underlying litigation, this research adopts various methodological fronts to investigate it. It uses documentary-bibliographic means (laws, doctrine, and jurisprudence), in a descriptive perspective, to contextualize the state of the art; a problematizing approach (case studies and data collection) on the limits of the system of judgment of repetitive cases in resolving global litigiousness; an exploratory study in the construction of the assumptions of approximation of the models (ontological, sociological-finalistic, and logical-systematic); without renouncing, later on, qualitative and quantitative analyses of statistics that are interpreted under the deductive method to draw conclusions and start the construction of bases that enable this symbiosis. By comparing these theoretical and practical elements, it became possible, even if preliminarily, to outline - in normative and potential links (lege ferenda) - an open and communicative system of joint treatment of collective and repetitive procedural techniques to address not only procedural litigation but also the underlying litigation, based on the idea of an integrative collectivization.